SYSTEM DYNAMIC ANALYSIS PERSPECTIVE IN DESIGNING THE SUSTAINABLE MOUNTAIN TOURISM MANAGEMENT MODEL - Aryanto, Rudy; Sarjono, Haryadi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
Ecotourism, one of the emerging tourism alternatives, is the result of the changes in the values and the habits of people. The rapidly growing ecotourism movement for mountain zone of tourism attraction, in this case just like the ecotourism in the Taman Nasional Gunung Halimun Salak (TNGHS), West Java. Ecotourism contains area of natural tropical biodiversity conservation, wildlife nature, rainforest scenery, local community, and others various natural potentials that can be beneficial to attract domestic tourists as well as international tourists. This study refers to the mountain ecotourism destination representing extreme virtues of landscape and nature. Mountain issues have been recognized by the international community as one of the world's most vulnerable bio-geographical areas susceptible to land degradation, having variable climates, heterogeneous habitats often with the unique fauna and flora. The study aimed to develop a dynamic model to understand the dynamic relationships between economy, environment and population. In this model several scenarios are analyzed which incorporate various policies and development paths. A dynamic simulation model tries to conceptual simulate the real situation or the real world to analyze the dynamic relations between the variables in the model. The dynamic model is used to see how developments and management of tourism destination may affect the conservation area. The main goal of this study is to obtain an insight into the dynamic interactions between the main factors influencing tourism. The results indicate that tourism shows a cyclical path, that policies to conservation the mountain not only have a positive effect on tourism but also on the rest of the economy.